DHR – Ready for take-off - Haschberger, B.; Hesse, J.; Heiden, M.; Seitz, R.; Schramm, W. (Hämostaseologie, 2009)
The collaboration between the Paul-Ehrlich-Institute (PEI) and the GTH as well as the two patient organisations, DHG and IGH has been official since February 2007 with the signing of the collaboration contract. In December 2008, the University of Munich started data enrollment. The DHR is a new software development which includes matters and modules of epidemiological as well as clinical cancer registries. Instead of collaborating with a trustee for personal data the DHR is using a so called “Intermediate”. Intermediate is an independent software module installed on a separate server without hard disk and with solely random access memory. It receives personal data from the treaters over the internet, calculates the pseudonyms, which are then forwarded to the database. The Intermediate needs to be protected from data access by the PEI and its operating system and software has to be started afresh with each start. These facts require the involvement of a trustworthy third party. It shuts Intermediate off from the PEI without itself coming into the possession of personal data.
Keywords: Haemophilia; registry; software; data safety